2020
DOI: 10.3847/1538-4365/ab579a
|View full text |Cite
|
Sign up to set email alerts
|

Relating Streamer Flows to Density and Magnetic Structures at the Parker Solar Probe

Abstract: The physical mechanisms that produce the slow solar wind are still highly debated. Parker Solar Probe's (PSP 's) second solar encounter provided a new opportunity to relate in situ measurements of the nascent slow solar wind with white-light images of streamer flows. We exploit data taken by the Solar and Heliospheric Observatory (SOHO), the Solar TErrestrial RElations Observatory (STEREO) and the Wide Imager on Solar Probe to reveal for the first time a close link between imaged streamer flows and the high-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…Rouillard, Kouloumvakos, et al. (2020) confirmed the relationship between mesoscale density structures observed in images and in situ by tracking larger streamer blobs with embedded approximately hourlong structures from STEREO SECCHI to their impact with Parker Solar Probe. In short, it is now clear that the solar wind is often formed of quasi‐periodic mesoscale plasma density structures released as a part of solar wind formation.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Rouillard, Kouloumvakos, et al. (2020) confirmed the relationship between mesoscale density structures observed in images and in situ by tracking larger streamer blobs with embedded approximately hourlong structures from STEREO SECCHI to their impact with Parker Solar Probe. In short, it is now clear that the solar wind is often formed of quasi‐periodic mesoscale plasma density structures released as a part of solar wind formation.…”
Section: Introductionmentioning
confidence: 67%
“…More recently, Rouillard, Kouloumvakos, et al. (2020) tracked density structures through the STEREO COR2 and HI1 FOVs to their impact at Parker Solar Probe, where they observed a one‐to‐one correlation between the 3–4 hr density structures observed remotely and the in situ Parker measurements. They showed that Parker measured additional sequences of small density peaks separated in time by approximately 90–120 min, suggestive of the types of periodic density enhancements at 90 min time scales that have been observed in situ at L1 (Kepko & Spence, 2003; Viall et al., 2008), near Mercury's orbit with Helios (Matteo et al., 2019), and remotely with STEREO (Viall & Vourlidas, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disconnections will certainly result in a decreased strahl intensity. The second source is interchange reconnection between open field lines and closed loops of streamers (Wang et al, 2000;Crooker et al, 2004;Rouillard et al, 2020). Individual interchange reconnection events, which change the magnetic connection into loops of different heights and electron temperatures, will almost certainly result in a change in the strahl intensity.…”
Section: The Electron Strahl and The Types Of Solar Wind Plasmamentioning
confidence: 99%
“…We observe some brightening located at the core of the northern streamer and some bright spike-like features that appear periodically near the streamer edges. These are transient perturbations of the streamer associated with the passage of two consecutive CMEs (Hess et al 2020;Rouillard et al 2020) indicated by two white arrows on the WISPR map. The southern streamer is more diffuse and exhibits much less activity with the exception of the passage of the first CME which originated in the northern streamer and was deflected southward during its transit through the corona to WISPR.…”
Section: Wispr Carrington Mapsmentioning
confidence: 99%